PARTISIPASI MASYARAKAT DALAM KONSERVASI HUTAN MANGROVE DI DESA KALIWLINGI KECAMATAN BREBES KABUPATEN BREBES - Muchammad Fikri Arvian Rachadi, - (2021)
Mangrove Forest on the Border of Central Java Province have potential for coastal abrasion and disasters and potential as a strategic area with its commodities but its existence is threatened by the lack of community participation in conserving the mangrove forest. The purpose of this study is to identify community participation in conserving Mangrove Forests. Survey methods with the entire population of residents living in Kaliwlingi Village, Brebes District, Brebes Regency from various circles and ages totaling 8769 residents. Cluster and residents sampling using random sampling technique by region (Cluster Random sampling system) done randomly by making residents from various circles and ages with data analysis using likert and chi-squared scales. The results of this study show that community participation is carried out with proper planning and implementation, however the contribution has not been optimal. This research is useful as an information input for the community, researchers, managers, and local governments in evaluating the management of Mangrove Forests as conservation areas, and ecotourism.